Perbandingan Viskositas, Titik Nyala dan Titik Beku Biodiesel dari Rumput Laut (Eucheuma denticulatum), Minyak Ikan Lemuru (Sardinellla longiceps) dan Biodiesel Komersil [ The Comparison of Viscosity, Flash Point and Freeze Point Biodiesel of Seagrass (Eucheuma denticulatum), Sardinella Oi] - Boedi Setya Rahardja; Woro Hastuti Satyantini; Andry Wijayanto (Faculty of Fisheries and Marine Universitas Airlangga, 2015)
Abstract Necessity of fuel are increasing rapidly nowadays. But oil is an irreversible product, so it is required to look for other alternative fuels, especially from renewable materials. Currently being developed technology that uses biodiesel as renewable alternative fuel. The aim of this research to determine whether oil and seaweed Eucheuma denticulatum and Lemuru fish oil can be used as materials for biodiesel. This research was conducted by observing and comparing the flash point, freeze point, and viscosity of each treatments. The Method in this research is experimental method and supported by panelist. There were 9 treatments in this study, there are P0 (Biodiesel commercial), P1 (Biodiesel Eucheuma denticulatum 100 %), P2 (Biodiesel Eucheuma denticulatum 75% + Biodiesel commercial 25%), P3 (Biodiesel Eucheuma denticulatum 50% + Biodiesel commercial 50%), P4 (Biodiesel Eucheuma denticulatum 25% + Biodiesel commercial 75%), P5 (Biodiesel Sardinella oil 100 %), P6 (Biodiesel Sardinella oil 75% + Biodiesel commercial 25%), P7 (Biodiesel Sardinella oil 50% + Biodiesel commercial 50%), and P8 (Biodiesel Sardinella oil 25% + Biodiesel commercial 75%). Each treatments was repeated 3 times. The main parameter observed was flash point, freeze point, and viscosity in every treatment. The data analysis used was non-parametric test with Friedman test and continued with Wilcoxon test. The results of this study indicate that the best of the nine treatments is P8 which is a mixture of lemuru fish oil biodiesel 25% and 75% biodieesel with the specifications freezing point -3oC, viscosity of 4.02 mm2 / s, and the flash point of 47.9oC.